The reality of the application of knowledge management processes in public schools in the North Eastern badia from the point of view of principals - Jaber, Anas Abdullah (Journal of Educational and Psychological Sciences, 2022)
The study aimed at revealing the reality of the application of knowledge management in public schools in the northeastern Badia Brigade from the point of view of its managers. The study has been checked for differences for gender changes, school level (basic-secondary), the place of school and scientific qualification on the reality of management Knowledge in public schools in the North-East Badia Brigade from the point of view of their managers. The descriptive approach has been used for such studies. The number of members of society (172) was director and manager, with a simple random sample, including 100 directors and director. To achieve the objectives of the study, a survey of (30) has developed a paragraph on the three study hubs: the axis of recognizing the concept of knowledge management, the focus of the implementation of knowledge management on the teaching process, the focus of the school role in providing knowledge management requirements. The sincerity of the question was confirmed on a group of competent and expertise, and the stability was carried out on the basis of the alpha Kronbach equation. The tool has achieved a high degree of stability (0.878).The study has shown very much consent on first study axes: the level of recognition of concept of knowledge and second: the focus of the implementation of knowledge management application on the teaching process, and the third: the axis of the school role in providing knowledge management requirements. The study also showed no statistically significant differences between school principals according to the study changes: sex, school level the, and school place. The researcher has come out of several recommendations, including: a recommendation for further research, especially a study on the application of knowledge management in public schools in the North East Badia Brigade.
Keywords: knowledge management; public schools; North Eastern Badia District; Jordan; school principals